Rare foreign body in bladder: A case report. Issue 17 (April 2018) - Li, Yubing; Gao, Yunqiu; Chen, Xiangdong; Jiang, Shaobo
Abstract: Rationale: The bladder is the most common site of foreign bodies in the urinary tract. Presenting complaints in patients with a foreign body are urinary retention, dysuria, frequent urination, decreased urine volume, nocturia, hematuria, painful erection, as well as pain in the urethra and pelvis. Patient concerns: A 50-year-old married male presented with complaints of severe lower abdominal pain and dysuria. Diagnoses: A plain radiograph of the pelvis showed a metallic dense foreign body that was composed of many small magnetic balls in the pelvic region. Interventions: The foreign body was removed under cystoscopy, and 67 magnetic balls were detected without any surgical or postsurgical complications. Outcomes: During operation, A cystoscopic examination confirmed no residue. Lessons: The bladder is the most common site of a foreign body in the urinary tract.Most intravesical foreign bodies can be removed transurethrally and with minimum access. The best mode of management depends on the nature of the foreign body, lodged site, expertise of the surgeon, and available instruments.